Academic Writing and the Internet: Cyber-Plagiarism amongst University Students - Nechita Olivia-Dumitrina; Montserrat Casanovas; Yolanda Capdevila (Springer, 2019)
This research aims to present a number of findings on the perception that university students have on academic plagiarism. Data has been collected on the procedures of copy and paste, paraphrase, translation, as well as the need for citation of resources taken from the Internet. This study was carried out at the University of Lleida (UdL), via an online questionnaire administered to 1150 first-year students. The results show similar figures in the understanding of plagiarism with respect to two procedures: copy and paste (69.3%) and paraphrase (68.3%). In the case of translation, the figure is higher with 82.1% of students considering that translating a text is plagiarism. Regarding the need to cite digital sources, 13.6% argue it is not necessary. When analysing the results according to the different faculties and affiliated schools, no pattern of behaviour has been detected in relation to the typology of the degree students were enrolled in, but a trend towards different behaviours can be observed in the two faculties in which students have received specific training within the framework of subjects of their degrees (Faculty of Nursing and Physiotherapy and Faculty of Education, Psychology and Social Work). In these cases, the figures related to acknowledging plagiarism procedures are higher and so is the percentage of students who say that resources taken from the Internet should be cited. This leads us to conclude, in line with other studies that have dealt with the same subject, that training is key to tackling the issue of plagiarism in higher education.